(3TQM GdEQTGOs - (3GdTeS eMeO Hf YHO GdefYe GdLhLQis; (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeGf HEQTGOghHYO aEf cJGH GdEQTGO bO CJi HeRjO Ydi CUdg cHjQ (B,(3hbO SCdfi HYV GdENhGf Cf CcJH Ydjg JYdjbkG jJcad HEVGM CdaGXg s
(3BNQgG (B:s
(3hZPG ELJeY Ydi GdEfSGf aQjVI HGdfPQ hLfGRI hYjO hcSha hNja GdahGJ HOC HaQjVI dCfgG Cge , Ke LfGRg NTjI s
(3cJH eJf GdEQTGO HGdMeQIs
(3YdjgG JedcGJ cKjQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdabg GdTGaYjs